Geospatial and Environmental Science Perspectives on Green Finance in East Africa: Integrating Climate, Hydrological, and Policy Analysis - Samatar, Elmi Hassan (Journal of Posthumanism, 2026)
Green finance has emerged as a critical instrument for advancing climate mitigation and sustainable development; however, its application in East Africa remains fragmented and insufficiently aligned with environmental system dynamics. This study examines the intersection of green finance, environmental processes, and geospatial analysis through a systematic bibliometric review using the PRISMA framework, supported by VOSviewer-based network and thematic analyses of 110 Scopus-indexed publications (2013-2025). The study further integrates a geospatial and environmental systems perspective, focusing on the climate-hydrology-land nexus. The study’s results indicate three key problems. Firstly, most studies have taken place in developed or emerging countries, and very few have included countries in East Africa. Secondly, most green finance studies have examined financial tools and policy implementation, but have not considered hydrology, water stress, or land-use change, all of which are important for sustainable development. Thirdly, techniques such as GIS and remote sensing, which can be used to evaluate environmental effects on projects under green finance, have been underused. Four major thematic areas emerged from this analysis: green finance and policy systems, climate change and sustainability, hydrological risk and geospatial monitoring; these are highly disconnected, indicating we need to explore ways to integrate these approaches. The study finds that, to have an impact on the ability to fund green projects in East Africa, it will require integrating financial instruments, environmental processes, and spatial analytical tools. The recommendations include using hydrology and land use as decision criteria when making financial investments, increasing transparency through enhanced geospatial monitoring, and improving governance, regulations, and financial inclusion. This study provides a basis for addressing significant gaps in current knowledge on how to develop green financing options tailored to a region’s specific geographic conditions, particularly for regions vulnerable to climate change impacts.